2014
DOI: 10.1371/journal.pone.0114604
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Enhances Chemotaxis of Primary Human B Cells during Asthma

Abstract: IL-17 is a pro-inflammatory mediator that is believed to play a critical role in regulating tissue inflammation during asthma, COPD, as well as other inflammatory disorders. The level of expression of IL-17 has been shown to be upregulated in lung bronchial tissue of asthmatic patients. Several reports have provided further evidence that this cytokine could play a key role in enhancing the migration of inflammatory as well as structural cells of the bronchial lung tissue during asthma and COPD. B cell infiltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…IL-17A receptor (IL-17RA) is ubiquitously expressed on many cell types of human body and highly expressed in the bone marrow, thymus, and spleen [ 55 ]. In the airways, IL-17RA is mainly expressed on fibroblasts, epithelial cells, smooth muscle cells, and microvascular endothelial cells [ 21 , 22 ]. However, the effect of IL-17RA on skin fibroblasts has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17A receptor (IL-17RA) is ubiquitously expressed on many cell types of human body and highly expressed in the bone marrow, thymus, and spleen [ 55 ]. In the airways, IL-17RA is mainly expressed on fibroblasts, epithelial cells, smooth muscle cells, and microvascular endothelial cells [ 21 , 22 ]. However, the effect of IL-17RA on skin fibroblasts has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro chemotaxis assay demonstrated IL-17A could stimulate the migration of B cells. Similarly, studies in inflammatory lung tissues showed that IL-17A could promote the migration of B cells [ 16 , 17 ]. Several studies have confirmed that B cells could express chemokine receptors CCR2 [ 28 ], CCR6 [ 29 ] and CXCR5 [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few reports concerning the effects of IL-17A on the migration and functions of B lymphocytes. Previous studies have demonstrated that IL-17 could recruit B cells in respiratory tissues [ 16 , 17 ]. However, whether IL-17 could promote the recruitment and tumor lysis of B cells in cancer remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Early IL-17 is required for protective immunity against the highly pathogenic H5N1 influenza virus infection demonstrated by a mechanism involving induction of CXCL13 and recruitment of CXCR5 + B cells into the lung tissue (31). Accordingly, IL-17 2/2 mice had increased inflammation and decreased total B cells in the lung (19,31), and in vitro, IL-17 axis blockade led to defects in chemotaxis of human B cells (41). These findings suggest that localization and organization of B cells in follicles were likely impaired without IL-17 signaling in these models.…”
Section: Friend or Foe: The Protective And Pathological Roles Of Indumentioning
confidence: 99%